All In One Civil Engineering PE Exam Guide: Reinforced Concrete Beams - Stirrup Spacing - Goswami, Indranil (McGraw-Hill's AccessEngineering., 2015)
This video demonstrates the calculation of stirrup spacing in a reinforced concrete beam.